Chapter 15 Family Firms and Family Constitutions in France – A General Overview - Katrin Deckert (Emerald Publishing Limited, 2023)
Ah la famille …! We tend to say that we do not choose it. But there are beautiful family stories, even in business, and particularly in France. Indeed, when it comes to business, the French take family as a serious matter – with about 80% of all companies in the country family controlled. Whether big or small, French family businesses are particularly noticeable in sectors such as food and beverages, as well as luxury. The chapter gives a general overview of family firms in France, considering in particular their main legal structures, how diverse they are in reality, and finally their governance rules, and notably their family constitutions. It concludes that business and family stories often prove to be a good match, at least in France.
10.1108/978-1-83797-200-520231015; 10.1108/978-1-83797-200-520231015; Family Firms and Family Constitution; EBP099697173